Testing weak-form efficiency of emerging economies: a critical review of literature - Nurunnabi, Mohammad (Journal of Business Economics and Management, 2012)
Due to the globalisation and mobilisation of capital markets, the concept of EMH is gaining a lot of importance in both developed and emerging economies. Most of the researches on the weak-form efficiency to date were based on the developed countries. The present study will seek to provide a comprehensive understanding of the weak-form efficiency in emerging economies. In terms of practical implications, the paper has direct implications for future research in EMH in particular emerging economies. The paper contributes in manly three ways: First, the paper collates and examines the broader and most effervescent literature and their findings. Second, it also presents a comprehensive, encompassing research work and a holistic view of various aspects of weak-form EMH. Finally, no studies have been conducted to date on a literature review of EMH weak-form efficiency in emerging economies. Nevertheless, the limitation of the study is that the findings are presented that may not be generalized to developed nations, which may be quite different in socio-cultural and political settings including the behavioral aspects of investors and the strength of the capital market. Article in English. Kritinė kylančios ekonomikos mažo rinkos efektyvumo literatūros apžvalga Santrauka. Dėl globalizacijos ir mobilizacijos kapitalo rinkose efektyvios rinkos hipotezės koncepcija įgyja vis didesnę svarbą tiek išsivysčiusiose, tiek sparčiai kylančios ekonomikos šalyse. Dauguma tyrimų, susijusių su mažu rinkos efektyvumu, buvo atliekami ekonomiškai stipriose valstybėse, tačiau šiame straipsnyje siekiama pateikti išsamų paaiškinimą apie mažą efektyvumą kylančios ekonomikos šalyse. Straipsnį sudaro trys dalys: pirmoji dalis skirta mokslinių darbų ir jų rezultatų analizei, antrojoje dalyje pateikiami autoriaus atlikto tyrimo rezultatai, susiję su efektyvios rinkos hipotezės reiškiniu, trečioji dalis susijusi su pagrindiniu šio straipsnio tikslu, t. y. kylančios ekonomikos mažo efektyvumo mokslinių darbų kritine analize įvairiose šalyse. Reikšminiai žodžiai: efektyvios rinkos hipotezė, mažas efektyvumas, rinkos efektyvumas, sparčiai kylanti ekonomika, Pietų Azija